PENDEKATAN STUDI ISLAM DALAM REHABILITASI PENYALAHGUNA NARKOBA - Amar Ma'ruf (Jurnal Penelitian Agama, 2018)
Abstract: Caring is a form of love and affection from a cultured social human. Narcotics in the view of Islam is an something haram if it is misused. Through caring, prevention of various crimes, juvenile delinquency, security, peace, harmony, will be easily done. With this caring attitude, the motto that, "Prevention is better than cure", will really be proven in cases of drug use. Narcotics is something familiar and in this article discusses the understanding and impact of drugs. It can be concluded that any type of drug abuse can damage the moral, physical and psychological condition of children. For that reason, parents must pay more attention to their children to avoid them from drug abuse. Keywords: Islamic studies, rehabilitation, and drugs.